A qualitative inquiry into pregnant women's perceptions of respectful maternity care during childbirth in Ibadan Metropolis, Nigeria. Issue 1 (31st December 2022) - Esan, Oluwaseun Taiwo; Maswime, Salome; Blaauw, Duane
Abstract: Women's perceptions of respectful maternity care (RMC) are critical to its definition and measurement globally. We evaluated these in relation to globally defined RMC norms. We conducted a descriptive study involving eight focus group discussions with 50 pregnant women attending antenatal clinic at one primary and one secondary health facility each in the North-west and South-west local government areas of Ibadan Metropolis, Nigeria. One focus group each with primigravidae and multiparas were held per facility between 21 and 25 October 2019. Shakibazadeh et al's 12 domains of RMC served as the thematic framework for data analysis. The women's perceptions of RMC resonated well with seven of its domains, emphasising provider-client inter-personal relationships, preserving their dignity, effective communication, and non-abandonment of care, but with mixed perceptions for two domains. However, their perceptions deviated for four domains, namely maintaining privacy and confidentiality; ensuring continuous access to family support such as birth companions; obtaining informed consent; and respecting women's choices about mobility during labour, food and fluid intake, and birth position. The physical environment was not mentioned as contributing to an experience of RMC. Whilst the perceptions of the Nigerian women studied about RMC were similar to those accepted internationally, there were significant deviations which may be related to cultural differences and societal disparities. Different interpretations of RMC may influence women's demand for such care in different settings and challenge strategies for promoting a universal standard of care.